Pemberdayaan Kelompok Wanita Tani (KWT) Kota Pala Melalui Inovasi Ecoenzym Untuk Pengelolaan Sampah Organik Rumah Tangga di Desa Dauh Peken Tabanan - L P K Pratiwi; I N A Guna; I M A Wigun; N M A W Utami; I W Terimajaya; I W Terimajaya (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
This Community Service Program aims to enhance the capacity of the Women Farmers Group (Kelompok Wanita Tani/KWT) Kota Pala in Dauh Peken Village, Tabanan District, Tabanan Regency through the innovation of eco-enzyme production as a circular economy-based solution for household organic waste management. The main problem faced by the partner community is the increasing volume of household organic waste, which is still managed conventionally without proper sorting and further processing. This condition leads to environmental pollution, declining village cleanliness, and limited community skills in converting organic waste into valuable products. The program was implemented through several stages, including socialization on the concept of organic waste management and eco-enzyme, technical training on eco-enzyme production using kitchen waste, assistance during the fermentation process, and evaluation of eco-enzyme utilization in agricultural and household activities. The results indicate a significant improvement in the knowledge and skills of KWT members in sorting organic waste and processing kitchen waste into eco-enzyme. The produced eco-enzyme was utilized as liquid organic fertilizer, botanical pesticide, and natural household cleaner, thereby reducing household waste volume while increasing community awareness of sustainable environmental management. In addition, this program opens opportunities for developing eco-enzyme as a group-based flagship product that supports the implementation of a village-level circular economy. Thus, empowering KWT through eco-enzyme innovation serves as an effective strategy for promoting sustainable household organic waste management and strengthening the economic independence of the community in Dauh Peken Village.